Unit Cost Analysis of Sectio Caesarea Using Activity-Based Costing - Girsang, Ermi; Nasution, Sri Lestari Ramadhani; Kurniawan, Andi (FORIKES, 2025)
Determining medical service tariffs, particularly for Sectio Caesarea (SC), is a critical decision that directly affects hospital profitability. To generate accurate cost information, an appropriate accounting system is essential, one of which is the Activity-Based Costing (ABC) method. This method is considered more precise than traditional approaches because it utilizes multiple cost drivers and allocates expenses based on actual activities. This study aimed to analyze the unit cost of SC procedures at RSU Royal Prima Medan using the ABC method. Conducted between April and June 2025, the study examined a one-year sample of 72 SC patients. Costs were categorized and analyzed across three activity levels: unit-level, batch-level, and facility-level. The findings revealed a total cost of SC services amounting to IDR 1,220,572,338, with an average cost per patient of IDR 16,952,394. After applying a 15% profit margin, the recommended tariff was IDR 19,495,253 per patient—lower than the hospital’s current rate of IDR 20,141,176, resulting in a difference of IDR 645,923. This discrepancy indicates that the ABC method offers a more realistic and accurate representation of actual costs, making it a valuable tool for evaluating operational efficiency and revising service tariffs. In conclusion, the application of the ABC method in determining C-section service rates enables hospitals to set tariffs that more accurately reflect resource consumption. It is recommended that hospitals adopt the ABC method comprehensively across all service units to enhance efficiency and promote cost transparency.Keywords: activity-based costing; unit cost; sectio caesarea; cost driver; cost efficiency